Diet Quality and Mindfulness as Predictors of Emotional Well-being in Adults With High Stress - Ben Amor, Leila; Mchedlidze, Nino (Mental Health and Lifestyle Journal, 2023)
This study aimed to examine the predictive roles of diet quality and mindfulness in emotional well-being among adults experiencing high levels of stress. A correlational descriptive research design was employed, involving a sample of 392 adults residing in Georgia. The sample size was determined based on the Morgan and Krejcie table to ensure statistical power. Participants were selected through stratified random sampling and completed standardized self-report instruments including the Warwick-Edinburgh Mental Well-being Scale (WEMWBS), the Healthy Eating Index–2015 (HEI-2015), and the Five Facet Mindfulness Questionnaire (FFMQ). Emotional well-being was the dependent variable, while diet quality and mindfulness were the independent variables. Data were analyzed using SPSS version 27. Pearson correlation coefficients were calculated to assess the relationship between emotional well-being and each predictor. Multiple linear regression analysis was performed to determine the combined predictive power of the independent variables. Results showed significant positive correlations between emotional well-being and both diet quality (r = .41, p < .01) and mindfulness (r = .52, p < .01). The multiple linear regression model was statistically significant, F(2, 389) = 91.84, p < .001, with an R² of .32, indicating that 32% of the variance in emotional well-being could be explained by the two predictors. Mindfulness (β = .39, p < .001) emerged as a slightly stronger predictor than diet quality (β = .27, p < .001). The findings indicate that both diet quality and mindfulness significantly and independently predict emotional well-being in adults with high stress. These results underscore the importance of integrated lifestyle interventions that promote both nutritional and psychological self-care strategies to enhance emotional resilience in high-stress populations.